Isolation and characterization of Paenibacillus polymyxa LY214, a camptothecin-producing endophytic bacterium from Camptotheca acuminata. (1st August 2015) - Pu, Xiang; Chen, Fei; Yang, Yun; Qu, Xixing; Zhang, Guolin; Luo, Yinggang
Abstract: Camptothecin (CPT) is mainly produced and extracted from Camptotheca acuminata and Nothapodytes foetida for pharmaceutical use, i.e., the starting material for chemical conversion to the clinical CPT-type drugs. As the third largest plant anticancer drug, the heavy demand on CPT from global market leads to many research efforts to identify new sources for CPT production. Herein we report the isolation and characterization of a CPT-producing endophytic bacterium Paenibacillus polymyxa LY214 from Camptotheca acuminata . A 10.7 μg l −1 of CPT was presented in the fermentation broth of P. polymyxa LY214. Its CPT production decreased sharply when the strain of the 2nd generation of P. polymyxa LY214 was cultured and fermented. However, the CPT production remained relatively constant from 2.8 μg l −1 of the 2nd generation to 0.8 μg l −1 of the 8th generation of P. polymyxa LY214 under optimized fermentation conditions. A 15- to 30-fold increase of CPT yield was observed when the optimized fermentation conditions, together with the addition of putative biosynthetic precursors of CPT and adsorbent resin XAD16, were applied to ferment the strains of the 7th and 8th generation of P. polymyxa LY214. Bioinformatics analysis of the relative species of P. polymyxa LY214 indicates its potential to produce CPT, which will be helpful to decipher the mysteries of CPT biosynthesis.